Measuring and Fostering Preservice Chemistry Teachers' Scientific Reasoning Competency - Besim Enes Bicak; Cornelia Eleonore Borchert; Kerstin Höner (MDPI AG, 2021)
Developing scientific reasoning (SR) is a central goal of science-teacher education worldwide. On a fine-grained level, SR competency can be subdivided into at least six skills: formulating research questions, generating hypotheses, planning experiments, observing and measuring, preparing data for analysis, and drawing conclusions. In a study focusing on preservice chemistry teachers, an organic chemistry lab course was redesigned using problem-solving experiments and SR video lessons to foster SR skills. To evaluate the intervention, a self-assessment questionnaire was developed, and a performance-based instrument involving an experimental problem-solving task was adapted to the target group of undergraduates. The treatment was evaluated in a pre-post design with control group (cook-book experiments, no SR video lessons) and alternative treatment group (problem-solving experiments, unrelated video lessons). Interrater reliability was excellent (ρ from 0.915 to 1.000; ICC (A1)). Data analysis shows that the adapted instrument is suitable for university students. First insights from the pilot study indicate that the cook-book lab (control group) only fosters students' skill in observing and measuring, while both treatment groups show an increase in generating hypotheses and planning experiments. No pretest-posttest differences were found in self-assessed SR skills in the treatment groups. Instruments and data are presented and discussed.